Surrogate endpoints of efficacy - Markman, Maurie (Henry Stewart Talks, 2018)
Improvement in overall survival must be considered the single most important goal of any new antineoplastic strategy, Also increasingly recognized that in well-defined settings it is reasonable to employ other objectively measurable endpoints of efficacy such as time to symptomatic disease progression, The rationale for the use of surrogate or alternative endpoints in cancer clinical trials, Examples of where such endpoints may be appropriately utilized